2009
DOI: 10.1111/j.1439-0507.2009.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in psoriatic patients - rationalization of systemic treatment

Abstract: Nail changes in patients with psoriasis have been reported with varying prevalence. Onychomycosis has been reported in up to 47% of the psoriasis patients. The purpose of this study was to determine the prevalence of nail abnormalities, onychomycosis in psoriasis and response to itraconazole treatment. We evaluated 312 patients suffering from psoriasis for nail changes and onychomycosis. Patients having laboratory confirmation of onychomycosis were treated with three courses of itraconazole (400 mg day(-1) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 16 publications
2
37
0
6
Order By: Relevance
“…6 Nail infections are less common in fingernails than in toenails, and the frequency is influenced by age, lifestyle or presence of concomitant diseases. 2 …”
Section: Discussionmentioning
confidence: 99%
“…6 Nail infections are less common in fingernails than in toenails, and the frequency is influenced by age, lifestyle or presence of concomitant diseases. 2 …”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten mit einer gleichzeitig bestehenden Gelenkmanifestation in Form einer Psoriasis arthropathica (PsA) wurde in bis zu 80 % der Fälle eine Nagelbeteiligung beobachtet [5,6]. Der von Psoriasis betroffene Nagel stellt zudem eine Prädilektionsstelle für die Entwicklung einer Nagelmykose dar [14,7]. Die Lebenszeit-Inzidenz der…”
Section: Epidemiologieunclassified
“…Hier kann sich ein "locus minoris resistentiae" ausbilden und die Infektion mit Pilzerregern signifi kant begünstigen. Die Häufi gkeit der Onychomykose bei Patienten mit Nagelpsoriasis wird auf 13-47 % beziffert [14]. Manchmal nehmen die Nägel eine weißliche oder undurchsichtige Fär-bung an, die als Leukonychie bezeichnet wird.…”
Section: Tüpfelnägel Entstehen In Folge Abnormerunclassified
“…The estimated prevalence of onychomycosis is more than 10% in the general population and 40% in elderly individuals, probably due to suboptimal immune function, inactivity, and the inability to maintain good foot care (5). It has been reported that the majority of onychomycoses are caused by dermatophytes, while yeasts and NDMs each account for approximately 10% of onychomycosis cases worldwide (3).…”
Section: Introductionmentioning
confidence: 99%